Arsenic Removal from Aqueous Solutions by Raw and Incinerated Pine Bark - Mojtaba Afsharnia (Journal of Global Pharma Technology, 2017)
In this research, raw and incinerated pine barks were evaluated as absorbents for the removal of pentavalent arsenic As(V), from aqueous solutions. After preparing artificial wastewater samples containing different concentrations of arsenic, the impact of the parameters including pH, adsorbent dosage, contact time and initial arsenic concentration was assessed on arsenate adsorption level by both of the absorbents. The results showed that the pine bark ash could remove arsenic from aqueous solutions better than the raw pine bark in optimum conditions of contact time of 60 minutes, pH 7, absorbent dosage of 1 g/l and initial arsenic concentration of 1000 µg/l with absorption efficiency of 95.86%. Considering the high efficiency of absorbent at neutral pH as well as the availability and low cost of the pine barks, the use of pine bark ash is suggested as an effective absorbent for removing arsenic from aqueous solutions.Keywords: Pine Bark, Arsenic, Aqueous Solutions